The International Bureau of Education: A Precursor of the Unesco and the Factory of its Pedagogical Guidelines? (1934–1968) - Hofstetter, Rita; Schneuwly, Bernard (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación)

(untitled) (Faculty of Education, Queen's University, 2020)
Our article contributes to tracing the sociogenesis of “educational internationalism” as promoted by the International Bureau of Education (IBE) when it became an intergovernmental organization in 1929, cooperating with Unesco since 1947, before being fully integrated in 1969. The IBE can be considered as one of the precursors of Unesco, a kind of factory of its pedagogical guidelines: it develops a modus operandi for producing, through a comparative approach, in as objective and neutral a manner as possible, knowledge concerning the progress of education in the world and recommendations forming a charter of world aspirations in education. These matters are discussed in International Conferences on Public Education (ICPE). With the birth of Unesco, the IBE negotiates a status of autonomy and collaboration, continuing its technical work based on comparative education. The problems studied, defined by both institutions together, relate to three crucial fields: access to education, curriculum, teacher education. The IBE’s approach is far from being free of tensions: in the results themselves of its work and between the countries participating in IBE’s inquiries and the ICPEs.